Interventional Radiology Management of Vascular Trauma in the Pelvis: Literature, Current Practice, and Strategies for the Future - Laidlaw, Grace L.; Shin, David S.; Abad-Santos, Matthew; Hua, Ethan W.; Vaji, Karim; Kogut, Matthew J.; Monroe, Eric J.; Som, Avik; Chick, Jeffrey F. B. (Seminars in Interventional Radiology, 2025)
The management of pelvic trauma has undergone a transformation with the advent of interventional radiologic techniques, particularly embolization procedures. Embolization allows for control of pelvic hemorrhage, utilizing real-time imaging to identify and treat injured vessels, thereby stabilizing patients and reducing the need for invasive surgical procedures. Through advanced imaging and evolving technologies, interventional radiologists continue to refine the management of pelvic trauma and improve clinical outcomes. This review describes the background and current endovascular management of pelvic trauma by IR.
Keywords: trauma; pelvis; embolization; hemorrhage; interventional radiology; vessel